The Indian Mutiny of 1857 and the Cape Colony : Part II : The Emergence of Black Consciousness in Caffraria (Historia, 2021)
A major effect of the Indian Mutiny on the Cape Colony was an urgent demand for troops and horses. But there is evidence that more than these material aspects was involved. It is clear that the Mutiny made a strong impression on the Blacks, and may be considered as a formative influence on Black cohesiveness in Caffraria, and, indeed, even on the emergence of Black consciousness itself. By Black cohesiveness is meant the emergence of some sort of common feeling among Blacks, of whatever tribe (people), that they were the Black people of Africa, drawn together by the universal threat of White territorial encroachment on their land and their way of life. By Black consciousness is meant the articulation by 1865 of this pervasive sense of ethnicity into a written statement by the Reverrend Tiyo Soga (1829-1871) which reflected pride of belonging to an ideal Africa-wide Black people, who were strong physically, tenacious culturally, and proud of their heritage and colour. It must be stressed that "Blackness" was an essential ingredient in this increasing sensitivity.
Keywords: Indian Mutiny; Caffraria; History; Rev. Tiyo Soga; Black conciousness; Blackness; Black people of Africa; 1857; Cape Colony; Historia; South African history